Pengaruh suhu operasi terhadap penentuan karakteristik pengeringan busa sari buah tomat menggunakan tray dryer - Tri Hariyadi (Jurnal Rekayasa Proses, 2018)
Food damage can be caused by intrinsic and extrinsic factors. The causes of intrinsic factors involve water activity (aw) and moisture content, the level of maturity and the nature of the food material itself. Meanwhile, the causes of extrinsic factors were the air composition, temperature, pressure, population and microbial contamination. Drying is one of the most widely used preservative methods, namely by evaporating most of the water contained in food by heat energy. This work studied the effect of operating conditions on the characteristics of tomato drying using tray dryer with the addition of foaming agent albumin and carrier agent dextrin which function as foam stabilizer. Tomatoes used as raw materials were ripe tomatoes, fresh red, and the same relative diameter, not physiologically and mechanically damaged. In this work, tomatoes were sliced, crushed for 10 minutes using blender, separated from the seeds and the residues with a 60-mesh sieve, and then mixed with dextrin and foaming agent albumin each as much as 5% weight. The mixture was blended for 10 minutes. The tray dryer was filled with hot air at 2.0 m/sec with temperature variation of 40, 50, 60 or 70°C. The stainless-steel dish containing tomato paste with thickness of 2 mm or 4 mm was inserted to the dryer. The tomato paste was weighted every 5 minutes. It is found, at a thickness of 2 mm, the optimum drying occurred at a temperature of 70 ℃ with critical time, tc, for 0.92 hours, critical water content of the sample, Xc, 1.40 %, and constant drying rate, Rc, 897.12 kg/m2.hour. In drying operations of 4 mm thickness, optimum drying occurs at 50 ℃ temperature with critical time, tc, for 1.92 hours, critical water content of sample, Xc, 2.56 %, and constant drying rate, Rc, 175.52 kg/m2.hour.